1983
DOI: 10.1210/endo-112-3-1042
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Gonadotropin-Releasing Hormone Receptorsduring Gonadotropin Surges in Ovariectomized-Estradiol-Treated Rats*

Abstract: In intact cycling rats, the number of pituitary GnRH receptors varies markedly during the estrous cycle. Concentrations are maximal on diestrus and early proestrus, before falling rapidly for a brief period immediately before the preovulatory gonadotropin surge. In this study we investigated whether dynamic changes in ovarian steroids, pituitary hormones, and GnRH itself, all of which are changing at the time of the surge, play a role in the acute transient down-regulation of the pituitary GnRH receptors. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In rodents, the relationship of pituitary GnRH receptor expression to LH surge generation is unclear. Some studies in OVX rats indicated that pituitary GnRH receptor expression decreases before an estradiolinduced surge (48), suggesting that estradiol exerts a negative feedback effect at the pituitary before the LH surge, making a GnRH surge critical for LH surge generation. Other studies, however, have indicated an increase in GnRH receptor mRNA before both proestrus and estradiol-induced surges that persists throughout the LH surge in rats (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, the relationship of pituitary GnRH receptor expression to LH surge generation is unclear. Some studies in OVX rats indicated that pituitary GnRH receptor expression decreases before an estradiolinduced surge (48), suggesting that estradiol exerts a negative feedback effect at the pituitary before the LH surge, making a GnRH surge critical for LH surge generation. Other studies, however, have indicated an increase in GnRH receptor mRNA before both proestrus and estradiol-induced surges that persists throughout the LH surge in rats (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…This decline may develop before [3,30] or dur ing [8,27] the LH surge, and it appears to be of a transient nature [3,27]. A similar reduction in receptor content can be induced in ovariectomized rats by the administration of es tradiol, at a dose capable of eliciting a proestrous-type of LH discharge [3],…”
Section: Discussionmentioning
confidence: 87%
“…Earlier findings have demonstrated that Nembutal blockade of either the proestrous LH surge [1,3,27] or of an Ej-induced LH release [3] prevents the associated decline in pituitary LHRH receptors. Our results confirm these obser vations in their entirety.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations